PENGGUNAAN MEDIA PERMAINAN KARTU KUARTET PANCASILA PADA MATA PELAJARAN PPKN UNTUK MENINGKATKAN PEMAHAMAN SISWA TENTANG PENERAPAN NILAI PANCASILA DALAM KEHIDUPAN SEHARI-HARI - Rizki Septa Hardhita Rizki Septa Hardhita (EduStream: Jurnal Pendidikan Dasar, 2022)
This study aims to determine the ability of students and the effect of using the Pancasila quartet card game media to increase students' understanding of the application of Pancasila values ​​in everyday life. The research method used is classroom action research with research procedures in the form of cycles. In the technique of collecting data, tests were carried out. The test is carried out to measure the ability of students before the action is taken and after the action is taken. The research instrument used was a written test as a means by which students were given assignments. The data analysis technique used is quantitative analysis. Quantitative analysis has characteristics that can be displayed in the form of numbers, in the form of initial learning outcomes and final learning outcomes. The result of this research is that the media of the Pancasila quartet card game is effective in increasing students' understanding of the application of Pancasila values ​​in everyday life. In the first cycle with the lecture method and power point media the percentage of students who got a complete score was 50%, when improvements were made in the second cycle with the quartet card game media, the percentage of students who got a complete score increased by 85%.